Collaborative Motor Learning Based on the Zone of Proximal Development - Ira Wahyu Lestari; Fauziah Hasan; Agus Sriyanto; Elyaum Farihah; Alan Lutfi Gesang Spautra (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2026)
This study explores the potential role of collaborative motor learning facilitated through the strategic arrangement of tools and spaces in supporting the development of social skills in early childhood. While social and motor skills are fundamentally interrelated, a significant knowledge gap persists regarding the operationalization of a learning environment that integrates both dimensions simultaneously. The novelty of this research lies in its explicit treatment of spatial and tool arrangements as concrete sociocultural instruments within the Zone of Proximal Development (ZPD) framework, an aspect often overlooked in traditional motor development studies. Employing a descriptive qualitative approach, the study involved children aged 5 to 6 years. Data were collected through participant observation, in-depth interviews, and documentation, then analyzed using the Miles and Huberman model. The findings indicate that the Cheerful Number Relay activity designed with an open spatial layout, a colored relay track, and visual composition boards demonstrates a significant contribution to fostering active social interactions. Children exhibited enhanced capacities in coordination, communication, mutual assistance, and self-regulation. These results confirm that collaborative motor learning, structured through systematic environmental interventions, functions as scaffolding to optimize social skills within the ZPD. This study provides practical contributions for early childhood educators in designing holistic learning environments that integrate social and motor competencies.